Linear/linear rational spline interpolation - Ideon, Erge; Oja, Peeter (Mathematical Modelling and Analysis, 2010)
For a strictly monotone function y on [a, b] we describe the construction of an interpolating linear/linear rational spline S of smoothness class C 1. We show that for the linear/linear rational splines we obtain ¦S(xi ) − y(xi )¦8 = O(h 4) on uniform mesh xi = a + ih, i = 0,…, n. We prove also the superconvergence of order h3 for the first derivative and of order h2 for the second derivative of S in certain points. Numerical examples support the obtained theoretical results.This work was supported by the Estonian Science Foundation grant 8313.First published online: 10 Feb 2011